Proceedings of the 4th International Conference on Foundations of Digital Games 2009
DOI: 10.1145/1536513.1536534
|View full text |Cite
|
Sign up to set email alerts
|

Addressing industry issues in a multi-disciplinary course on game design

Abstract: Over the past few years, games courses have been gaining in popularity, as there has been growing evidence showing positive enrollment and student engagement results. Nevertheless, new graduates still lack critical teamwork and problemsolving skills required by industry employers. Building upon other game programs that had successful results, we present a game design course developed to attract students of all disciplines. Our course is different because we focus on three main issues directly associated with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The course at UVic is different from other game courses as it is a multi-disciplinary course heavily stressing collaborative work, group orientation, and peer review activities [7]. Art and writing students are not expected to be core team programmers, but must be able to effectively communicate with the programmers on their respective teams to succeed.…”
Section: Background and Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…The course at UVic is different from other game courses as it is a multi-disciplinary course heavily stressing collaborative work, group orientation, and peer review activities [7]. Art and writing students are not expected to be core team programmers, but must be able to effectively communicate with the programmers on their respective teams to succeed.…”
Section: Background and Related Workmentioning
confidence: 99%
“…The content of the Fall 2009 course on game design was very similar to the previous offering of the course at UVic that we introduced in the Fall 2008 semester [7]. The main activities we restructured were those involving peer review; where possible, we preserved the other aspects of the course so that we could get an accurate assessment of how our new peer review activities affected student engagement.…”
Section: Course Structurementioning
confidence: 99%
See 1 more Smart Citation
“…A growing mass of descriptive research has recently been published outlining the development of games-related courses which sit within the existing curricula of traditional computer science (CS) and engineering disciplines-see, for instance, Jones [2000], Burns [2008], Volk [2008], Zyda et al [2008], Coller and Scott [2009], and Duvall [2009]. However, the motive for the inclusion of games material in traditional study pathways is often reported to be that of stimulating interest in more traditional subject areas, particularly CS, which have experienced continued reductions in student numbers in recent years [Carter 2006;Defoe et al 2011;Estey et al 2009;Morrison and Preston 2009;Rocco and Yoder 2007]-a point which invariably fuels the concern among those in the games industry who reject the true validity of such courses.…”
Section: Introduction To Computer and Video Games Coursesmentioning
confidence: 99%
“…Recent research on the contents of game development curricula identified an 'expectation gap ' (McGill, 2009) between industry and academia which needs to be addressed. Estey et al (2009) acknowledge that games graduates still lack the necessary employability skills and call for a more generic curriculum. In the UK context, academics are guided by the Quality Assurance Agency's (QAA) benchmark for computing which states that graduates should demonstrate transferable skills such as 'managing one's own learning', communication, team-working and organizational skills (QAA, 2007).…”
mentioning
confidence: 99%